The BUILDING LEARNERS’ CONCEPTUAL KNOWLEDGE AND DIGITAL LITERACY WITH PBL-BASED E-STUDENT WORKSHEET: - - Purwati, Yeni Sri; Distrik, I Wayan; Ertikanto, Chandra (International Journal of Research -GRANTHAALAYAH, 2023)
The objective of this research was to see the role of the electronic student worksheet based on Problem-Based-Learning (PBL-based E-SW) to build conceptual knowledge and digital literacy. This research used a static pretest-posttest design. The population was students in Padangcermin Public Senior high School, in Pesawaran. Samples were taken by cluster random sampling, and they consisted of 35 students in the experiment classroom and 35 students in the control classroom. The experiment classroom was taught using PBL-based E-SW and the control classroom was taught using worksheet used to teach in the school. The result showed that there was a significant influence of using PBL-based E-SW to build conceptual knowledge and digital literacy of students. Paired sample t-test result was less than 0.05, and this indicated a significant difference in average n-gain scores between the experiment and control classrooms. The average n-gain scores on conceptual knowledge were 0.61 or belonging to a moderate category in the experiment classroom and 0.41 or belonging to a moderate category in the control classroom. The average n-gain scores on digital literacy were 0.89 or belonging to a high category in the experiment classroom and 0.67 or belonging to a moderate category in the control classroom.